2020
DOI: 10.3390/diagnostics10080522
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Angiotensin Receptor–Neprilysin Inhibitors on Myocardial Function in Chronic Heart Failure Patients with Reduced Ejection Fraction

Abstract: Background. We sought to evaluate the long-term effects of angiotensin receptor blocker–neprilysin inhibitor (ARNI) therapy on reverse remodeling of the failing myocardium in HFrEF patients. Methods. We performed a prospective non-randomized longitudinal study on 228 HFrEF patients treated with ARNI at our center. Prior to ARNI introduction all patients received stable doses of ACEI/ARB for at least six months. Clinical, biochemical and echocardiography data were obtained at ARNI introduction and 12-month foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The pooled data from 8 studies 13 , 14 , 15 , 22 , 23 , 24 , 25 , 28 (732 patients) showed increases in TAPSE (WMD, 1.26 mm; 95% CI, 0.33 to 2.18 mm; I 2 =78.3%; Figure 1 and Table S2 ). Two studies 14 , 24 (186 patients) reported data on S’, which was improved after the treatment with S/V (WMD, 0.85 cm/s; 95% CI, 0.25–1.45 cm/s; I 2 =0.0%; Figure 1 and Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The pooled data from 8 studies 13 , 14 , 15 , 22 , 23 , 24 , 25 , 28 (732 patients) showed increases in TAPSE (WMD, 1.26 mm; 95% CI, 0.33 to 2.18 mm; I 2 =78.3%; Figure 1 and Table S2 ). Two studies 14 , 24 (186 patients) reported data on S’, which was improved after the treatment with S/V (WMD, 0.85 cm/s; 95% CI, 0.25–1.45 cm/s; I 2 =0.0%; Figure 1 and Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The mean follow‐up duration ranged from 3 to 17.1 months. Of the 10 included studies, 6 13 , 15 , 22 , 23 , 24 , 25 were prospective, and 4 14 , 26 , 27 , 28 were retrospective. One study 24 had a control group that received angiotensin‐converting enzyme inhibitor, whereas the others had no control group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations